2021
DOI: 10.1016/j.lanepe.2021.100177
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among people living with HIV in England and the Netherlands: a population-based study

Abstract: Background HIV is now considered a chronic condition, and people living with HIV, when treated, have a similar life expectancy as compared to the general population. Consequently, improving and ensuring a good health-related quality of life (HrQoL) among people living with HIV (people living with HIV) is increasingly important and has risen on the global agenda in recent years. A ‘fourth 90’ as 90% of people with viral load suppression have a good HrQoL should therefore be adopted alongside the ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
2
15
2
Order By: Relevance
“…The EF and GHP domains showed the lowest scores overall, which is in line with these recent studies [41,42]. Overall, cultural and country-specific differences need to be considered in the assessment of HRQL [37].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The EF and GHP domains showed the lowest scores overall, which is in line with these recent studies [41,42]. Overall, cultural and country-specific differences need to be considered in the assessment of HRQL [37].…”
Section: Discussionsupporting
confidence: 88%
“…Overall, PLWH and significant fibrosis may characterize a population at risk that needs closer monitoring and counseling to improve the negative impact on HRQL. Previous studies have often highlighted a higher prevalence of mental health problems, including anxiety and depression, in PLWH [37,38]. In our study, the mental health domain had an overall lower score compared to other domains, although no difference was seen in the fibrosis subgroup.…”
Section: Discussioncontrasting
confidence: 53%
“…[ 44 ] Popping et al recently found a high prevalence of anxiety/depression in PLWH compared with the general population, especially if patients were >60 years of age. [ 25 ] Notably, older age remained independently associated with low HRQL in the subgroup analysis without HS in this study. Although the anxiety/depression dimension was prominent in both subgroups, they were not significantly different from each other.…”
Section: Discussionmentioning
confidence: 55%
“…Overall, the differences in these HRQL findings may be multifactorial and country‐specific. [ 25 ] According to previous studies, low socioeconomic status and income are often associated with low HRQL. [ 40 ] We were not able to see an effect of unemployment or education level on the HRQL in PLWH and without HS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation